Evaluation of the pulmonary vein ostia during the cardiac cycle using electrocardiography-gated cardiac computed tomography in cats - Kim, Junyoung; Kim, Dae-Hyun; Kim, Kitae; Oh, Dayoung; Choi, Jihye; Yoon, Junghee (Frontiers in Veterinary Science, 2022)
Several studies in humans have provided detailed descriptions of the anatomy of the pulmonary veins (PVs) and their ostia for the implementation of thoracic interventions, such as radiofrequency ablation, for patients with atrial fibrillation. These studies have shown that electrocardiography (ECG)-gated multidetector computed tomography (MDCT) can evaluate the dimensional variations in the PVs or ostium according to the cardiac cycle. However, few studies have examined the PVs or ostia using MDCT in veterinary medicine. Therefore, this study investigated the variation in the diameter of the PV ostium in cats during the cardiac cycle using ECG-gated MDCT and determined the correlation between the size of the heart or left atrium (LA) and diameter of the PV ostium. This study included six cats, including five normal animals and one cat with hypertrophic cardiomyopathy. The PVs were found to drain into the LA via three ostia, i.e., the right cranial ostium, left cranial ostium, and caudodorsal ostium. Moreover, a diametric variation was observed in all PV ostia according to the cardiac cycle phase on ECG-gated MDCT: the maximal diameter was observed at the end of ventricular systole, and the minimal diameter was observed at the end of ventricular diastole for each PV ostium. There were no significant correlations between the heart or LA size and maximal or minimal diameter of each of the three PV ostia (p>0.05); however, the enlargement of each PV ostium at the end of ventricular systole differed significantly from that at the end of ventricular diastole. This study suggested the clinical feasibility of ECG-gated MDCT in providing more detailed anatomical information about the PVs, including the dimensional changes during the cardiac cycle in cats. Based on this study, knowledge of the variations in the PV ostium offers interesting avenues for research into the effect of PV function. Furthermore, ECG-gated MDCT could allow for greater clinical application of interventional procedures in animals with various cardiac diseases.